Vestibular migraine - Santosh Kumar Swain; Sampada Munjal; Suryakanta Pradhan (Apollo Medicine, 2021)
Vestibular migraine (VM) is a distinct clinical entity which accounts for major vestibular symptoms among the adult and children. It is now accepted as a major cause for episodic vertigo. The pathophysiology for VM is not completely understood and is always a puzzling dilemma. Patients often present with vertigo, headache, photophobia, and phonophobia. The clinical examinations and laboratory investigations are usually within normal limit. The diagnosis of VM is often challenging as there are no confirmatory tests available. The treatment is often similar to the migraine headache. The present-day recommendation is to use the same prophylactic medications used for migraine including beta-blockers, antidepressants, and anticonvulsants. It is always a challenging disease for clinician and often creates a puzzle for diagnosis and treatment. Proper diagnosis and treatment of VM need a thorough understanding of the current literatures which are discussed details in this review article.